Ensuring efficient use of the resource potential of the enterprise - Sikorska, Małgorzata; Pererva, P. G. (NTU "KhPI", 2017)
In the conditions of scientific and technical progress, the growth of capital productivity of fixed assets, which in modern conditions is complicated by rapid change of equipment, and also by an increase in capital investments directed at improving working conditions, is of great importance for the effective use of the resource potential of the enterprise.
Keywords: potential; enterprise; efficient; technical progress